The ACCENT-VOCBAS field campaign on biosphere-atmosphere interactions in a Mediterranean ecosystem of Castelporziano (Rome): site characteristics, climatic and meteorological conditions, and eco-physiology of vegetation - Fares, S; Mereu, S; Scarascia Mugnozza, G; Vitale, M; Manes, F; Frattoni, M; Ciccioli, P; Gerosa, G; Loreto, F (Biogeosciences, 2009)
Biosphere-atmosphere interactions were investigated on a sandy dune Mediterranean ecosystem in a ﬁeld campaign held in 2007 within the frame of the European Projects ACCENT and VOCBAS. The campaign was carried out in the Presidential estate of Castelporziano, a periurban park close to Rome. Former campaigns (e.g. BEMA) performed in Castelporziano investigated the emission of biogenic volatile organic compounds (BVOC). These campaigns focused on pseudosteppe and evergreen oak groves whereas the contribution of the largely biodiverse dune vegetation, a prominent component of the Mediterranean ecosystem, was overlooked. While speciﬁc aspects of the campaign will be discussed in companion papers, the general climatic and physiological aspects are presented here, together with information regarding BVOC emission from the most common plant species of the dune ecosystem. During the campaign regular air movements were observed, dominated by moderate nocturnal land breeze and diurnal sea breeze. A regular daily increase of ozone concentration in the air was also observed, but daily peaks of ozone were lower than those measured in summer on the same site. The site was ideal as a natural photochemical reactor to observe reaction, transport and deposition processes occurring in the Mediterranean basin, since the sea-land breeze circulation allowed a strong mixing between biogenic and anthropogenic emissions and secondary pollutants. Measurements were run in May, when plant physiological conditions were optimal, in absence of severe drought and heat stress. Foliar rates of photosynthesis and transpiration were as high as generally recorded in unstressed Mediterranean sclerophyllous plants. Most of the plant species emitted high level of monoterpenes, despite measurements being made in a period in which emissions of volatile isoprenoids could be restrained by developmental and environmental factors, such as leaf age and relatively low air temperature. Emission of isoprene was generally low. Accounting for the high monoterpene spring emission of the dune ecosystem may be important to correct algorithms at regional and ecosystem levels, and to interpret measurements of ﬂuxes of volatile isoprenoids and secondary pollutants.
Keywords: BVOC emission; Castelporziano; Mediterranean ecosystem; stress (voyant); Water availability

EMISSION OF SHORT CHAINED ORGANIC ACIDS , ALDEHYDES AND MONOTERPENES FROM QUERCUS ILEX L . AND PINUS PINEA L . IN RELATION TO PHYSIOLOGICAL ACTIVITIES , CARBON BUDGET AND EMISSION ALGORITHMS - Kesselmeier, J; Bode, K; Hofmann, U; Mtjller, H; Schafer, L; Wolf, A; Ciccioli, P; Cecinato, A; Frattoni, M; Foster, P; Dutaur, L; Torreq, L (Atmospheric Environment, 1997)
We report on the emission of monoterpenes, short-chained organic acids and aldehydes from Mediterranean oak (Quercus ilex L.) and pine (Pinus pinea L.). All studies were done with dynamic cuvettes enclosing intact branches at the top of the canopy flushed with ambient air. Daily trends are compared with the photosynthetic active radiation (PAR), leaf temperature and the physiological activities of the enclosed branches, i.e. assimilation and transpiration, with special attention on the carbon budget. Oak emits monoterpenes in high amounts, up to 2% of the assimilated carbon. As compared with monoterpenes, short-chained organic acids and aldehydes are of minor importance for oak. However, on a leaf dry-weight basis equal amounts of acids and aldehydes are released from oak and pine. As pine emitted only low amounts of terpenes (below 0.2% of the assimilated carbon) the release of terpenes and oxygenated compounds is of equal importance for this species. A comparison of a modelled light and temperature driven emission with the observed volatile organic compounds (VOC) emissions showed good agreement for monoterpenes as well as for organic acids emitted in the case of oak. For pine only the release of acids showed an adequate relation to the algorithm data, whereas the terpene emissions seemed to be dominated by temperature effects
Keywords: aldehydes; carbon budget; coniferous; deciduous; light; Monoterpenes; oak; organic acids; pine; Pinus pinea L; Plant physiology; Quercus ilex L; Temperature; Volatile Organic Compounds

Different sources of reduced carbon contribute to form three classes of terpenoid emitted by Quercus ilex L leaves - Loreto, F; Ciccioli, P; Brancaleoni, E; Cecinato, A; Frattoni, M; Sharkey, T D (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE UNITED STATES OF AMERICA, 1996)
Quercus ilex L. leaves emit terpenes but do not have specialized structures for terpene storage. We exploited this unique feature to investigate terpene biosynthesis in intact leaves of Q. ilex. Light induction allowed us to distinguish three classes of terpenes: (i) a rapidly induced class including alpha-pinene; (ii) a more slowly induced class, including cis-beta-ocimene; and (iii) the most slowly induced class, including 3-methyl-3-buten-1-ol. Using C-13, we found that alpha-pinene and cis-beta-ocimene were labeled quickly and almost completely while there was a delay before label appeared in linalool and 3-methyl-3-buten-1-ol. The acetyl group of 3-methyl-3-buten-1-yl acetate was labeled quickly but label was limited to 20% of the moiety. It is suggested that the ocimene class of monoterpenes is made from one or more terpenes of the alpha-pinene class and that both classes are made entirely from reduced carbon pools inside the chloroplasts. Linalool and 3-methyl-3-buten-1-ol are made from a different pool of reduced carbon, possibly in nonphotosynthetic plastids. The acetyl group of the 3-methyl-3-buten-1-yl acetate is derived mostly from carbon that does not participate in photosynthetic reactions. Low humidity and prolonged exposure to light favored ocimenes emission and induced linalool emission. This may indicate conversion between terpene classes.
APS
Keywords: acetyl group labelling; alpha-pinene; light induction; monotherpenes; Quercus ilex L.; terpenes biosynthesis

EMISSION OF MONOTERPENES AND ISOPRENE FROM A MEDITERRANEAN OAK SPECIES QUERCUS ILEX L. MEASURED WITHIN THE BEMA (BIOGENIC EMISSIONS IN THE MEDITERRANEAN AREA) PROJECT EMISSIONS IN THE M E D I T E - Kesselmeier, J; Fer, L S C H; Ciccioli, P; Brancaleoni, E; Cecinato, A; Frattoni, M; Foster, I P; Jacob, V; Denis, J; Fugit, J L; Dutaur, L; Torres, L; et al. (Atmospheric Environment, 1996)
We report on some results of our studies of monoterpene and isoprene emissions and the physiological activities of an oak species (Quercus ilex L.) under the Mediterranean climatic conditions found at Castel Porziano (Rome) in June 1993. The oak species Quercus ilex L. was found to emit mainly monoterpenes in high amounts. Isoprene emissions were negligible. Diel cycles of monoterpene emissions showed correlation with light and the diel behaviour of photosynthetic CO2 assimilation, transpiration and stomatal corductance. Temperature dependence seemed to be of minor importance.
Keywords: Biogenic emission; isoprene; light; Monoterpenes; non-methane hydrocarbons; oak; Plant physiology; VOC

Evidence of the photosynthetic origin of monoterpenes emitted by Quercus ilex L leaves by C-13 labeling - Loreto, F; Ciccioli, P; Cecinato, A; Brancaleoni, E; Frattoni, M; Fabozzi, C; Tricoli, D (PLANT PHYSIOLOGY, 1996)
The carbon of the four main monoterpenes emitted by Quercus flex L. leaves was completely labeled with C-13 after a 20-min feeding with 99% (CO2)-C-13. This labeling time course is comparable with the labeling time course of isoprene, the terpenoid emitted by other Quercus species and synthesized in leaf chloroplasts. It is also comparable with that of phosphoglyceric acid. Our experiment therefore provides evidence that monoterpenes emitted by Q. ilex are formed from photosynthesis intermediates and may share the same synthetic pathway with isoprene. By analyzing the rate and the distribution of labeling in the different fragments, we looked for evidence of differential carbon labeling in the alpha-pinene emitted. However, the labeling pattern was quite uniform in the different fragments, suggesting that the carbon skeleton of the emitted monoterpenes comes from a unique carbon source.
APS
Keywords: alpha-pinene; C-13 labeling; Emissions; isoprene; Monoterpenes; Quercus flex L.; Quercus ilex

Influence of environmental factors and air composition on the emission of alpha-pinene from Quercus ilex leaves - Loreto, F; Ciccioli, P; Cecinato, A; Brancaleoni, E; Frattoni, M; Tricoli, D (PLANT PHYSIOLOGY, 1996)
We studied the emission of alpha-pinene from Quercos ilex leaves. Only the abaxial side of the hypostomatous Q. ilex leaf emits alpha-pinene. Light induced photosynthesis and alpha-pinene emission. However, the response of photosynthesis to dark-to-light transitions was faster than that of alpha-pinene, suggesting that ATP controls the emission. The emission was higher at 30 than at 20 degrees C, whereas photosynthesis did not change. Therefore, the relationship between photosynthesis and alpha-pinene emission does not always hold. When CO2 was removed from the air, transpiration was stimulated but photosynthesis and alpha-pinene emission were inhibited. alpha-Pinene inhibition was more rapid under low O-2. When CO2 in the air was increased, photosynthesis was stimulated and transpiration was reduced, but alpha-pinene emission was unaffected. Therefore, the emission depends on the availability of photosynthetic carbon, is not saturated at ambient CO2, and is not dependent on stomatal opening. The pattern of alpha-pinene emission from Q. ilex is different from that of plants having specialized structures for storage and emission of terpenes. We suggest that alpha-pinene emitted by Q. ilex leaves is synthesized in the chloroplasts and shares the same biochemical pathway with isoprene emitted by isoprene-emitting oak species.
APS
Keywords: alpha-pinene; photosynthesis; Quercus ilex